Analisis Genetik Arsitektur Malai Padi Menggunakan Dua Populasi F2 - Ramadhan, Fitrah; Bayuardi Suwarno, Willy; Nindita, Anggi; Aswidinnoor, dan Hajrial (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Improvement of rice panicle architecture is one important objective in the development of improved new-plant-type rice varieties. Panicle architecture is directly related to yield components in rice. The aims of this study were to obtain information on inheritance pattern of panicle architecture on F2 generation and to obtain the best selected individuals. The experiment was conducted at Sawah Baru Experimental Farm Bogor, from May to October 2016. Two F2 populations derived from crosses of IPB 3S/IPB160-F-36, IPB160-F-36/IPB 5R and three genotypes of parents were used as experimental materials. A total of 208 and 204 plant samples were taken representing each of the two F2 populations and 20 plants representing the parents. Three panicles were taken randomly from each individual as observed samples. The results showed that additive gene action influenced number of primary branches in population of IPB 3S/IPB160-F-36, whereas in the population of IPB160-F-36/IPB 5R, most of the panicle architecture traits were controlled by additive gene action except for the length of primary branches. All of panicle architecture traits were controlled by relatively many genes except length of primary branches and number of grains on primary branches in the IPB 3S/IPB160-F-36 population. The panicle architecture of the two observed population was genetically varies. The heritability estimates were moderate to high. Selection could increase the mean of panicle architecture traits using either single or multiple traits simultaneously.Keywords: gene action, heritability, genetic variability, panicle traits